LOCAL GASTRONOMIC POINTS AS PART OF SUSTAINABLE AGRITOURISM AND YOUNG PEOPLE'S PERCEPTION OF IT. CASE STUDY, SIBIU COUNTY, ROMANIA - Mirela STANCIU; Agatha POPESCU; Cristian STANCIU; Sonia POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The work highlights the importance of local gastronomic points (LGP) in the sustainable development of villages in the mountain area of Romania. The paper employed a quantitative and a qualitative analysis. In this paper there are presented the number of local gastronomic points established in the mountain area of Sibiu County, Romania, the number of local producers registered under the optional "mountain product" quality scheme and the number of tourist structures with accommodation function and their accommodation capacity, from the same localities. A case study of a local gastronomic point was carried out and an investigation was carried out regarding the knowledge of young people about local gastronomic points, respectively their role in the development of villages.